Image-Based 3D Modeling as a Documentation Method for Zooarchaeological Remains in Waste-Related Contexts - Macheridis, Stella (Ethnobiology Letters, 2015)
During the last twenty years archaeology has experienced a technological revolution that spans scientific achievements and day-to-day practices. The tools and methods from this digital change have also strongly impacted archaeology. Image-based 3D modeling is becoming more common when documenting archaeological features but is still not implemented as standard in field excavation projects. When it comes to integrating zooarchaeological perspectives in the interpretational process in the field, this type of documentation is a powerful tool, especially regarding visualization related to reconstruction and resolution. Also, with the implementation of image-based 3D modeling, the use of digital documentation in the field has been proven to be time- and cost effective (e.g., De Reu et al. 2014; De Reu et al. 2013; Dellepiane et al. 2013; Verhoeven et al. 2012). Few studies have been published on the digital documentation of faunal remains in archaeological contexts. As a case study, the excavation of the infill of a clay bin from building 102 in the Neolithic settlement of Ҫatalhöyük is presented. Alongside traditional documentation, infill was photographed in sequence at each second centimeter of soil removal. The photographs were processed with Agisoft Photoscan. Seven models were made, enabling reconstruction of the excavation of this context. This technique can be a powerful documentation tool, including recording notes of zooarchaeological significance, such as markers of taphonomic processes. An important methodological advantage in this regard is the potential to measure bones in situ in for analysis after excavation.